Pengembangan Pedal Efek Gitar Elektrik Menggunakan Arduino - Martin Clinton Tosima Manullang; R. Rizal Isnanto; Eko Didik Widianto (Jurnal Teknologi dan Sistem Komputer, 2015)
The guitar has become common entertainment show at the moment. Devices Arduino controller board is present as a central processing for a variety of processing requirements, one of which is processing the sound. So the goal is achieved from this study was to test the Arduino as a controller device that is used in the effect processing. This study uses the waterfall method of development. Steps being taken begins with identifying needs and then proceed with the process of designing both the hardware and software. Then proceed with the testing design. In the testing phase used 3 kinds of testing, those are hardware testing, test using the software, and testing using respondents. The test results showed that the Arduino can be used as a controller of guitar sound processing with two inputs and outputs. It was also found that the true bypass pedal interface can change the path of the guitar input to be routed directly to the output. Other interfaces available on the system is also functioning as it should and can set values that affect the processing of voice. Based on the test results with the respondents, producing a sound that is quite good, has a full feature, and quite easy to operate.